A Domain-Specific Language to Specify Planned Architectures of Adaptive Systems - San Martín, Daniel; Camargo, Valter (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2021)
Adaptive Systems (ASs) are able to monitor their own behavior and adapt it when quality goals are not accomplished. MAPE-K is a reference model that provides abstractions to design ASs. Structuring such systems with these abstractions brings many benefits, some related to maintenance and some related to comprehension of the architecture. However, many existing ASs are not designed according to MAPE-K, making those abstractions hidden in their architecture. Architectural Conformance Checking (ACC) is a technique for checking if the current architecture (CA) of a system is obeying the rules prescribed by a planned architecture (PA) or even by a reference model, like MAPE-K. In this paper we present DSL-Remedy, a language for specifying PAs in the context of Adaptive Systems. Our language provides adaptive-systems specific abstractions so that engineers can be more precise when describing the planned architecture. Besides, as our DSL is ASs-specific, it incorporates some rules already known in MAPE-K. We have evaluated our DSL comparing it with a general-purpose DSL and the results show improvements in the productivity.